2019
DOI: 10.1109/tgrs.2019.2908517
|View full text |Cite
|
Sign up to set email alerts
|

Digital Terrain Model Retrieval in Tropical Forests Through P-Band SAR Tomography

Abstract: This paper focuses on the retrieval of terrain topography below dense tropical forests by means of synthetic aperture radar (SAR) systems. Low-frequency signals are needed to penetrate such a thick vegetation layer; however, this expedient alone does not guarantee proper retrieval. It is, here, demonstrated that the phase center of P-band backscatter may lie several meters above the ground, depending on the slope and incidence angle. SAR tomography is shown to overcome this problem and retrieves the actual top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 33 publications
0
34
0
Order By: Relevance
“…Since commonly available global Digital Elevation Models (DEM) are estimated from sensors operating at higher frequencies than P-band (e.g., Tandem-X or SRTM [42]), the elevation model may not correspond to the real terrain level, due to the limited penetration capabilities of higher frequencies into natural media. Thus, a suitable DTM will be produced from BIOMASS data themselves by using the full 3D information achievable from multi-baseline tomographic data [43] in the TOM phase.…”
Section: Agb Retrievalmentioning
confidence: 99%
See 1 more Smart Citation
“…Since commonly available global Digital Elevation Models (DEM) are estimated from sensors operating at higher frequencies than P-band (e.g., Tandem-X or SRTM [42]), the elevation model may not correspond to the real terrain level, due to the limited penetration capabilities of higher frequencies into natural media. Thus, a suitable DTM will be produced from BIOMASS data themselves by using the full 3D information achievable from multi-baseline tomographic data [43] in the TOM phase.…”
Section: Agb Retrievalmentioning
confidence: 99%
“…Another critical point is that an accurate DTM is required for the height estimation algorithm to be unbiased. To minimize the impact of this uncertainty the algorithm is expected to use the terrain elevation of the DTM derived during the tomographic phase [43], similarly to the ground cancellation described in Section 3.1.…”
Section: Fh Productmentioning
confidence: 99%
“…Tomographic profiles returned by the back-projection algorithms when applied to (a) real airborne data and (b) simulated spaceborne stack. The two axes are analogous to the ones shown in Figure 5; the black line shows the ground topography below the forest layer estimated through SAR tomography [25].…”
Section: Cross Sensor Simulationmentioning
confidence: 99%
“…The knowledge of precise terrain topography allows focusing the signal at a specific height with respect to the terrain rather than in an absolute reference, resulting in the generation of intensity maps associated with a specific height inside the vegetation layer [16]. Precise DTM can be estimated from multi-baseline data themselves thanks to the long wavelength [17]. An example of tomographic focusing is shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…The BIOMASS tomographic phase [18] will provide the first global coverage during the first 14 months of operations, by collecting seven ascending and seven descending passes with 3-days repeat pass time, designed to maintain coherency at P-band [19]. Thanks to the long wavelength of about 70 cm it will be possible not only to characterize electromagnetic interactions of radar waves with the forest structure and generate AGB maps over tropical biomes, but also to generate a global map of terrain topography below the vegetation layer (DTM) [17] and subsurface features [20,21]. Previous studies reported that a TomoSAR intensity of 30 m canopy layer in dense tropical forests is strongly correlated to AGB [22][23][24], whereas the ground scattering alone is poorly correlated to biomass.…”
Section: Introductionmentioning
confidence: 99%